Life Cycle Assessment for Solid Waste Management: A Case Study for Melikgazi Municipality (Kayseri) - Emine Irbaş; Filiz Dadaşer Çelik (Doğal Afetler ve Çevre Dergisi)
Solid waste production increases rapidly due to population growth and technological developments. Reducing negative impacts from solid wastes requires the development of integrated management approaches that consider environmental sustainability. Life cycle assessment is one of the tools that can be used to assess environmental impacts of products and processes. In this study, the alternative management scenarios for solid wastes were examined using life cycle assessment approach for the Melikgazi Municipality, Kayseri. Four scenarios were identified. In Scenario 1, all wastes are collected, transferred to landfill site and landfilled. In Scenario 2, recyclable wastes are partially separated at the source and the remaining wastes are transferred and landfilled. In Scenario 3, all recyclable wastes are separated at the source and other wastes are landfilled. In Scenario 4, after separation of recyclable wastes, other wastes are either composted (50%) or landfilled (50%). Life cycle assessment for all scenarios was based on IWM (Integrated Waste Management) model. Net energy use / non-renewable energy resources depletion potential (GJ), global warming potential (kg CO2-equivalent), acidification potential (kg SO2-equivalent) and eutrophication potential (kg O2-equivalent) were calculated for all scenarios. For Melikgazi Municipality, Scenario 3 and 4 provided more advantageous alternatives in terms of energy consumption and environmental impacts. Separating recyclable wastes at the source has been effective in reducing environmental impacts. In addition, composting application has created less environmental impact compared to landfilling.